The Stimulus to Violence and its impacts on Mental Health of the Population: A context in the Brazilian Elections / O Estímulo à Violência e seus impactos na Saúde Mental da população: Um contexto vivenciado nas Eleições Brasileiras - Gonçalves Júnior, Jucier; Amorim, Liromaria Maria de; Farias, Athena de Albuquerque; Rolim Neto, Modesto Leite (ID on line. Revista de psicologia, 2019)
In 2018 the presidential dispute in Brazil fomented a series of violent acts throughout the country drawing the attention of the national and international press. Due to the psychological suffering inflicted on the population by the increasing rates of violence in Brazil, aggravated in the last three months in the run-up to the election, it was decided to reflect on mental health in the context of the Brazilian presidential elections. The studies show that where elections are competitive there is a greater probability of electoral violence occurring. Underdeveloped countries appear to be more amenable to this phenomenon because of excessive inequality of distribution / access to resources and political power. The main impacts on the mental health of the population are exacerbation of basic psychiatric conditions (such as schizophrenia and other psychotic disorders); increased fear, insecurity and sadness that produce psychic suffering in the population; and suffocation of social relations by preventing the process of socialization and the full use of spaces to collectivities. Therefore, the debates surrounding the mental health of these populations should be stimulated as they are fundamental for eliciting interdisciplinary public policies that align social and health needs.